2017
DOI: 10.1109/tits.2016.2591321
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Automatic Maritime Surveillance Systems With Visual Information

Abstract: Automatic surveillance systems for the maritime domain are becoming more and more important due to a constant increase of naval traffic and to the simultaneous reduction of crews on decks. However, available technology still provides only a limited support to this kind of applications. In this paper, a modular system for intelligent maritime surveillance, capable of fusing information from heterogeneous sources, is described. The system is designed to enhance the functions of the existing Vessel Traffic Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 23 publications
(28 reference statements)
0
42
0
1
Order By: Relevance
“…Similar works focus on the geographical and temporal nature of the data, and very often, those are presented within geovisual analytics, for example, Vatin and Napoli (, ). More specific work on the visualization of outliers appears in Etienne et al () while integrating visual information in existing VTS systems is the focus of Bloisi, Iocchi, Nardi, and Fiorini () and Bloisi, Previtali, Pennisi, Nardi, and Fiorini ().…”
Section: User Aspectsmentioning
confidence: 99%
“…Similar works focus on the geographical and temporal nature of the data, and very often, those are presented within geovisual analytics, for example, Vatin and Napoli (, ). More specific work on the visualization of outliers appears in Etienne et al () while integrating visual information in existing VTS systems is the focus of Bloisi, Iocchi, Nardi, and Fiorini () and Bloisi, Previtali, Pennisi, Nardi, and Fiorini ().…”
Section: User Aspectsmentioning
confidence: 99%
“…St-Charles method (St. Charles et al, 2015) suggested a new approach using spatio temporal binary similarity descriptors that could handle local changes in the frame due to the camouflage issue. Bloisi et al (2017) developed a modular system for the intelligent surveillance of maritime which fused on the information captured from heterogeneous sources. This work also helps environment protection issues along with dangerous threats coming from the sea such as fishing, illegal smuggling, immigration, piracy and oil spills.…”
Section: Related Workmentioning
confidence: 99%
“…Radar systems with an Automatic Radar Plotting Aid track unique live targets whose attributes can later be stored for post hoc analysis (Nohara et al, 2008). Satellite images, digital photographs, and video can also be used to supplement vessel and activity detection and tracking (e.g., Taborda and Silva, 2012;Bloisi et al, 2017;Bartholomew et al, 2018;James et al, 2019). The Marine Monitor (M2) is a low-cost proprietary coastal monitoring system developed by ProtectedSeas (2019) that integrates these multiple components including AIS, off-the-shelf marine radar, and a high-definition camera.…”
Section: Introductionmentioning
confidence: 99%